Effect of particle density in turbulent channel flows with resolved oblate spheroids. (30th April 2019) - Eshghinejadfard, Amir; Hosseini, Seyed Ali; Thévenin, Dominique
Highlights: Lattice Boltzmann simulations of turbulent particulate flows with heavy and neutrally-buoyant oblate spheroids are compared. Heavy particles considerably change the fluid and particle statistics. Heavy particles cause a higher reduction of the fluid streamwise velocity compared to the neutrally-buoyant ones. The concentration of heavy oblate spheroids increases gradually all the way up to channel center. Abstract: The present paper studies the effect of particle density in a turbulent channel flow laden with resolved oblate spheroids at a frictional Reynolds number of Re τ = 180 . Direct numerical simulations are performed by using the lattice Boltzmann method (LBM) for solving the flow field. Particle-fluid interactions are modeled by the immersed boundary method (IBM). Simulations are done for dense regimes of heavy and neutrally-buoyant particles with a volume fraction of 5%. The particle-fluid density ratios are 8.0 and 1.0 for heavy and neutrally-buoyant particles, respectively. Results show that particle inertia can significantly modify the fluid and particle statistics. Heavy particles cause a higher reduction of the fluid streamwise velocity with respect to the single-phase flow. Turbulence is attenuated by both particle types but the reduction is stronger with heavy particles than that with neutrally-buoyant ones. Moreover, increasing the density of particles is found to create smaller but more energetic vortices. Quadrant analysis shows that the contribution of ejection and sweep events in the Reynolds shear stress reduce on increasing the particle density. The local volume fractions of the two particle types are also seen to be different. While the volume fraction of neutrally-buoyant particles reach a constant value at a certain distance from the walls, the concentration of heavy oblate spheroids increases gradually all the way up to channel center. Both particle types show preferential orientation near the walls, where the symmetry axis is normal to the wall. However, this preferential orientation is less pronounced when increasing the particle inertia. Finally, the translational velocity fluctuations of heavy particles are found to be higher in the streamwise direction, but lower in the wall-normal direction.